A study on initial formation stage of proton irradiation defects in reactor pressure vessel steel - Ting Hao; Xueqing Liu; Bijin Zhou; Yuanfei Li; Chaoliang Xu; Xiangbing Liu; Weibin Jiang; Qianfeng Fang; Tao Zhang (Nuclear Materials and Energy)
The irradiation effect of a reactor pressure vessel (RPV) steel subjected to the proton irradiation with a dose of approximately 1 dpa and an energy of 240 keV at room temperature is investigated using the internal friction (IF) method. An evident IF relaxation peak at 357 °C has been detected in the proton-irradiated RPV sample but not in the as-received RPV sample. Based on theoretical analysis and experimental results in the references, this IF peak is believed to be associated with the formation of carbon-vacancy complexes (CmVn, specifically 4C2V-type). The gradual disappearance of the IF peak in the second and third IF heating spectra up to 400 °C indicates the dissolution of the proton-irradiation-induced CmVn complexes. Nanoindentation measurements and X-ray diffraction (XRD) strain analysis show the corresponding changes similar to the results of the IF measurement. The current study promotes an understanding of the influence of irradiation-induced CmVn complexes on the irradiation-induced hardening mechanism of the RPV steel, particularly during the initial formatiom stage of irradiation defects.